Geometric modeling and finite element analysis of kevlar monolithic and carbon-kevlar hybrid woven fabric unit cell. (2020) - Sharma, Pawan; Priyanka, Pragati; Mali, Harlal Singh; Dixit, Anurag
Abstract: The prediction of the mechanical strength of composites must be known before use or fabrication. The computerized modeling and analysis helps in prediction of the realistic performance of the composite products. The current research work presents the modeling routs of yarns, yarn interpolation for path, cross-section, and orientations with finite element analysis of woven fabric reinforcements. The geometrical modeling routes of textile woven reinforcements at meso-scale described by using TexGen 3.10, which is a python scripted software package, developed by the polymer composites group at the University of Nottingham, UK, works as a preprocessor for characterization of textile reinforcements. The finite element analysis of textile woven reinforcements is done by using a commercially available software package ABAQUS 6.14-5. Due to the similarity of python scripted codes in both the software's, ABAQUS is considered as an analysis tool for textile reinforcements among the so many FE based platforms. Textile woven fabric unit cell having plain and twill weaving patterns are explained with Kevlar (monolithic) and Carbon-Kevlar (hybrid) yarns with finite element compression behaviour analysis, and discussed to understand the mechanical performance of polymer textile composites.